2001
DOI: 10.1128/aac.45.12.3437-3444.2001
|View full text |Cite
|
Sign up to set email alerts
|

P-113 d , an Antimicrobial Peptide Active against Pseudomonas aeruginosa , Retains Activity in the Presence of Sputum from Cystic Fibrosis Patients

Abstract: Antimicrobial peptides are a source of novel agents that could be useful for treatment of the chronic lung infections that afflict cystic fibrosis (CF) patients. Efficacy depends on antimicrobial activity against the major pathogens of CF patients, Pseudomonas aeruginosa, Staphylococcus aureus, and Haemophilus influenzae, in the environment of the CF patient's airway. We describe the in vitro efficacies of derivatives of histatins, which are histidine-rich peptides produced by the salivary glands of humans and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 45 publications
0
77
1
1
Order By: Relevance
“…Similarly, the all-D-amino-acid isomer of Hsn5 12-mer (P113-D) was as active against C. albicans as the natural L form. In addition, P113-D but not the L peptide was active against respiratory bacteria in the presence of sputum from cystic fibrosis patients (23).…”
mentioning
confidence: 99%
“…Similarly, the all-D-amino-acid isomer of Hsn5 12-mer (P113-D) was as active against C. albicans as the natural L form. In addition, P113-D but not the L peptide was active against respiratory bacteria in the presence of sputum from cystic fibrosis patients (23).…”
mentioning
confidence: 99%
“…when standard MIC determinations were performed in RPMI 1640 or PG broth (containing 1% peptone) (data not shown). A similar inhibitory effect, caused by medium components, was previously observed when other anticandidal peptides were tested and was solved by using nonstandardized synthetic media (26,27). However, these alternative media were not suitable for testing the susceptibility of the Candida strains to kaliocin-1 due to the presence of an inhibitory salt concentration.…”
Section: Resultsmentioning
confidence: 65%
“…Similar salt-sensitive antimicrobial activity has been reported for many antimicrobial peptides and proteins, including defensins, histatin 5, lactoferricin, LL-37, lactoferrin, and synthetic antimicrobial peptides such as novispirin G10 (4,6,13,14,19,29,33). Although similar experimental low-salt conditions are not encountered in biological fluids, which brings into question the potential therapeutic application of these compounds, most peptides exhibit antimicrobial activities in vivo (24,27). It will be necessary to perform in vivo assays with Lfpep and kaliocin-1 to determine their potential value as therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…They are both derived from histatins, which are histidine-rich peptides produced by the salivary glands of humans. It has been suggested that histatins may be used to combat Pseudomonas aeruginosa infections in the airways of cystic fibrosis patients (21). It would be interesting to study the effect of histatins on Hsp16.3 on one hand and on mycobacterial viability on the other.…”
Section: Discussionmentioning
confidence: 99%